2013
DOI: 10.5798/diclemedj.0921.2013.02.0253
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of respiratory functions of athletes engaged in different individual sports branches

Abstract: Objectives: It was aimed to research pulmonary functionsof sedentary males and athletes who engaged in differentindividual sports branches in the same age group.Methods: 50 male athletes in 15-16 age group in the starcategory participated from each of the branches of judo,athletics, wrestling, taekwondo, table tennis and swimmingand 50 sedentary males participated as well; beingin total 350 subjects. Among respiratory functions tests;vital capacity (VC), forced vital capacity (FVC) and maximumvoluntary ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In the study on comparison of breathing functions of young team sportsmen from individual sports branches, Atan, Akyol, and Çebi (2013) found that breathing function of professional sportsmen was higher than others. They also found that different breathing functions of sportsmen from different branches might mean that the branch of sports involved statistically affected the overall breathing capacity of the sportsmen.…”
Section: Discussionmentioning
confidence: 99%
“…In the study on comparison of breathing functions of young team sportsmen from individual sports branches, Atan, Akyol, and Çebi (2013) found that breathing function of professional sportsmen was higher than others. They also found that different breathing functions of sportsmen from different branches might mean that the branch of sports involved statistically affected the overall breathing capacity of the sportsmen.…”
Section: Discussionmentioning
confidence: 99%
“…In previously performed similar studies, it is stated that the increase in FVC and FEV 1 values of male children aged 12-14 who do regular exercise is significant compared to the pre-training period [35], FVC values in young females aged 16 are higher in the athletes doing athletics compared to the control group [20], VC, FVC, FEV 1 and MVV values of female students aged between 11 and 14 playing volleyball are higher than those not doing sports [26], the FVC, FEV1, MVV ratio were higher in athletes than in the normal sedentary control individuals [4,15,29,40], the PEF and FEF 25/75 values of the training program applied for 3 months on the sedentary children in the age group of 10-16 are significant compared to the pre-training period [37] and in similar studies performed on children athletes in different branches, it is stated that PEF and FEF 25/75 values significantly differ after the exercise [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that control group does not exist in many of the researches performed to determine to what extent sports affects the respiratory parameters of children and youth and a complete standardization has not been established in terms of respiratory functions yet may cause different opinions in this topic. While some researchers advocate that intense physical exercises increase the respiratory parameters [4,11,23,24,33,34,42], some others state that this development is in parallel with the normal growth totally as the dynamic of age group [7,12]. Some other researchers suggest that exercise does not increase respiratory parameters, but also brings them to an efficient and economic condition [3].…”
Section: Introductionmentioning
confidence: 99%
“…When observations in the respiratory phase are evaluated, two or more parameters of lung volume capacities should be evaluated together (Çakmakçı et al, 2005). In our study, the respiratory parameters that we found to be meaningful were forced vital capacity (FVC) while the other was the maximal respiratory gas volume (FEV 1 ) (Atan et al, 2013). In literature, studies in this area are usually limited to pre-exercise and immediate after measures.…”
Section: Discussionmentioning
confidence: 99%